Identification of bacterial diversity in the feces of children with diarrhea - Rusdianto, Rusdianto; Nuha, Ulin; Wahyuni, Diah; Amaliyah , Tsabitah (Biology Education Department, Universitas Insan Budi Utomo, Malang, Indonesia, 2022)
Diarrhea diseases collectively constitute a serious public health challenge globally, especially as the leading cause of death in children. This study aims to identify the diversity of bacteria that cause diarrhea in children. This type of research is cross-sectional with a prospective descriptive approach. Sampling of 50 children with diarrhea in several health centers in Makassar City. The instrument used in this study was to use a list of questions related to the suitability of the desired sample and a descriptive chart of gram-negative bacteria and adapted to Bergey's Manual of Determinative Bacteriology to identify the bacteria obtained. The process of testing specimens with the culture method by isolation and inoculation of samples for further biochemical tests including Triple Sugar Iron Agar (TSIA), Indole Motility Sulfite (SIM), Methyl Red (MR), Vogas Proskauer (VP), and carbohydrates tests were carried out at the Microbiology Laboratory of Hasanuddin University Hospital. The results showed that the Escherichia coli bacteria were 15 (30%), Klebsiella sp as many as 14 (28%), Enterobacter sp as many as 12 (24%), Proteus mirabilis as much as 4 (8%), Proteus vulgaris as much as 4 (8%), and the bacteria Alcaligenes faecalis only 1 (2%). The conclusion of the study was that the most common type of bacteria found was Escherichia coli.